Pengaruh Media Booklet terhadap Peningkatan Pengetahuan dan Sikap Anak dalam Memilih Makanan Jajaan Sehat pada Anak Sekolah Dasar di SD Negeri 104244 Jati Sari Lubk Pakam - Erlina Nasution; Hany Putri Hidayat; Urbanus Sihotang (Lembaga Pengembangan Kinerja Dosen, 2024)
Snacks are food and drinks prepared or sold by street vendors on the streets and in public places that are eaten or consumed immediately without further processing or further preparation. However, according to the KLB from 2019-2022, food poisoning reached 23.36%. BPOM also found that 42 times (14.4%) of food poisoning came from snacks. Objective: to determine the effect of booklet media on increasing children's knowledge and attitudes in choosing Healthy Snacks for students at SDN 104244 Jati Sari Lubuk Pakam.Method: Pre- Experimental research type with a One Group Pre- Post Test research design which only used the Experimental group without a control/comparison group. The population in this research was students in grades IV and V, namely 53 people. Data collection was carried out by interviews. using a questionnaire sheet and analysis using the T-dependent test.Results: Research results showed that at the beginning of the research the knowledge score before the intervention was given in the form of counseling was 10.51 and after the intervention was given it increased to 20.06, while the attitude score before the intervention was given in the form of counseling was 17.79 and after the intervention increased to 21.06. The results of the T-test concluded that the media The booklet can increase knowledge and attitudes in choosing healthy snacks at SD Negeri 104244 Jati Sari Lubuk Pakam. Conclusion: There is effect on the knowledge and attitudes of elementary school children after being given counseling using booklet media. (p=0.000).